2015
DOI: 10.3727/096368914x684042
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Human Induced Pluripotent Stem Cell-Derived Neural Precursors in Spinal Cord Injury Repair

Abstract: Despite advances in our understanding and research of induced pluripotent stem cells (iPSCs), their use in clinical practice is still limited due to lack of preclinical experiments. Neural precursors (NPs) derived from a clone of human iPSCs (IMR90) were used to treat a rat spinal cord lesion 1 week after induction. Functional recovery was evaluated using the BBB, beam walking, rotarod, and plantar tests. Lesion morphology, endogenous axonal sprouting, graft survival, and iPSC-NP differentiation were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
83
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 55 publications
8
83
0
2
Order By: Relevance
“…The expression profile corresponds to previous flow cytometry analysis of the same iPSC-NPs during pre-differentiation in vitro. 20,43 The presence of A2B5 and CD44 in differentiating cells confirms the heterogeneity of the differentiating population and is also in agreement with Romanyuk et al 43 Increased expression of the neuronal marker β-III-tubulin during differentiation corresponds to our immunocytochemical data. The majority of differentiating cells were positive for β-III-tubulin and NF160.…”
supporting
confidence: 79%
“…The expression profile corresponds to previous flow cytometry analysis of the same iPSC-NPs during pre-differentiation in vitro. 20,43 The presence of A2B5 and CD44 in differentiating cells confirms the heterogeneity of the differentiating population and is also in agreement with Romanyuk et al 43 Increased expression of the neuronal marker β-III-tubulin during differentiation corresponds to our immunocytochemical data. The majority of differentiating cells were positive for β-III-tubulin and NF160.…”
supporting
confidence: 79%
“…To arrive at robust conclusions, data were discussed when an outcome was reported from at least three simultaneous comparisons. In our present meta-analysis, we included six publications with eight comparisons [26][27][28][29][30][31]. The most obvious finding to emerge from our analyses was that in rats with SCI, iPSC transplantation significantly promotes the locomotor recovery according to the BBB score.…”
Section: Discussionmentioning
confidence: 92%
“…In our metaanalysis, only one publication [27] mentioned the use of triple drug immunosuppression containing Cyclosporine A (10 mg/kg), azathioprine sodium (2 mg/kg), methylprednisolone (2 mg/kg, tapered to 0.5 mg/kg) and methylprednisolone (2 mg/kg, tapered to 0.5 mg/kg) to prevent graft rejection. Generally, it is necessary to use initial combined immunosuppressive therapy in order to achieve consistent cell survival at intervals of 2-2.5 months after grafting [46].…”
Section: Discussionmentioning
confidence: 99%
“…A number of these studies reported significant therapeutic benefit when NSCs/NPCs derived from either mouse (Tsuji et al, 2010) or human (Fujimoto et al, 2012; Nori et al, 2011; Romanyuk et al, 2014) iPS cells were transplanted into contusion or cavity-type models of rodent SCI, as well as in non-human primate models (Kobayashi et al, 2012). Unlike our current work, these studies did not focus on, or achieve, targeted replacement of astrocytes in the injured spinal cord.…”
Section: Discussionmentioning
confidence: 99%